Caught in the act… a case of fulminant amoebic colitis. Issue 4 (19th August 2015) - Gardiner, Bradley J.; Simpson, Ian; Woolley, Ian J.
Abstract : Introduction: Amoebic colitis is a common worldwide infection with a risk of serious complications, including invasive intestinal and extra-intestinal disease. Although newer tests are available, the mainstay of diagnosis remains stool microscopy. Early treatment with metronidazole followed by paromomycin generally results in a clinical cure. Case presentation: We describe a case of fulminant colitis secondary to Entamoeba histolytica requiring bowel resection that went unrecognized until the operative histology was reviewed. Conclusion: Clinicians worldwide need to be aware of this condition, particularly in patients originating from endemic areas, to ensure early diagnosis and appropriate treatment leading to optimal clinical outcomes.